THE EFFECTS OF CLINICAL, LABORATORY, and ANGIOGRAPHIC FACTORS ON STENT THROMBOSIS and MAJOR ADVERSE CARDIAC EVENTS IN PACLITAXEL ELUTING STENTS - Kandemir, Hasan Çağlayan; Baytugan, Nart Zafer (Sanamed, 2023)
Background: Drug-eluting stents (DES) have higher marked efficacy and lower revascularization requirements compared to bare metal stents (BMS). We aimed to determine the mid-term outcomes of patients implanted with first-generation DES “paclitaxel-eluting stents” (PES).  Methods: Patients with at least 1 PES implanted in our cardiology clinic were received in the non-randomized group. Inclusion criteria were all patients undergoing percutaneous coronary intervention and PES implantation. The mean follow-up time was 35.14 + 13.4 months.Results: A total of 302 patients (401 lesions and 337 PES) were enrolled in the study. The mean age was 61.86 + 10.27 years. Major adverse cardiac and cerebrovascular events (MACE) occurred at 17.9%, and the stent thrombosis rate was 4%. Independent predictors of stent thrombosis were serum creatinine levels [OR 1.59; 95% CI, 1.03-2.46, p=0.03] and mean platelet volume [OR 1.59; 95% CI, 1.03–2.46, p= 0.03]. Also, poor functional capacity [OR 2.46: 95% CI, 1.42- 4.26, p
Keywords: Paclitaxel; restenosis; thrombosis; real-world